If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h + 6 = 2h + 8 Reorder the terms: 6 + 4h = 2h + 8 Reorder the terms: 6 + 4h = 8 + 2h Solving 6 + 4h = 8 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 6 + 4h + -2h = 8 + 2h + -2h Combine like terms: 4h + -2h = 2h 6 + 2h = 8 + 2h + -2h Combine like terms: 2h + -2h = 0 6 + 2h = 8 + 0 6 + 2h = 8 Add '-6' to each side of the equation. 6 + -6 + 2h = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 2h = 8 + -6 2h = 8 + -6 Combine like terms: 8 + -6 = 2 2h = 2 Divide each side by '2'. h = 1 Simplifying h = 1
| 3-7*(3+4x)=-18 | | 8x+7=43+2x | | -y^2+5y+6=0 | | 2n+13=29 | | 5x^2+32x+12=0 | | n^2+17n+72=0 | | 2q^2=8q | | 10b+8=32 | | Plotx=4 | | k^2-11k+30=0 | | d^2-5d=0 | | -2x^2-5x+8=0 | | 24x^2-7x=0 | | 125x^3-216=0 | | 3r+6=5r+12 | | 3m=-15 | | 6+h=-3 | | 4+5x=-x-8 | | 2n+3=-18 | | y-4(0)=0 | | x^3-3x^2-4x+12= | | -8+6(3x+5)=-25 | | 3x^2+14x=5 | | 5x=-4 | | -5(p+2)=(2p-15)+p | | 2x+0=4 | | 3(x-8)=-15 | | (x-9)(5x+8)=0 | | 3(9-2)-9=x | | 5(3+6)+3(4-3)=x | | 6x-2y=12 | | 3+2(y-8)=11 |